An athletes [sic] performance: Can a possessive apostrophe predict success?: Misplace apostrophes, miss out on med school?. Issue 3 (7th March 2017) - Cop, Michael; Hatfield, Hunter
Abstract : If we believe social media, newspapers, and even some of our best friends and colleagues, the war over standard usage is on. As with many wars, the opposing sides seem to be entrenched in differing ideological positions and many of the battles seem to take place over the most unstable, smallest bits of territory - such as the Oxford comma, singular they, or split infinitives. In this ongoing war, possessive apostrophes have attracted particularly aggressive forays. For example, when some English cities proposed removing apostrophes from street signs, various news outlets published headlines such as, 'It's a catastrophe for the apostrophe in Britain' ( NBC, 31 January, 2009), 'Dropped apostrophes spark grammar war in Britain' ( New York Times, 16 March, 2013), and '"It's pandering to the lowest common denominator": Anger as Cambridge bans apostrophe from street names' ( Daily Mail, 18 January, 2014). Explaining Birmingham's ban, one city councillor was not that much less sensational, stating that apostrophes 'denote possessions that are no longer accurate, and are not needed' and that 'they confuse people. If I want to go to a restaurant, I don't want to have an A-level (high school diploma) in English to find it' ( NBC ).